Evaluating postgraduate family medicine supervisor feedback in registrars' learning portfolios - Neetha J. Erumeda; Ann Z. George; Louis S. Jenkins (AOSIS, 2022)
Background: Postgraduate supervision forms a vital component of decentralised family medicine training. While the components of effective supervisory feedback have been explored in high-income countries, how this construct is delivered in resource-constrained low- to middle-income countries has not been investigated adequately. Aim: This article evaluated supervisory feedback in family medicine registrars' learning portfolios (LPs) as captured in their learning plans and mini-Clinical Evaluation Exercise (mini-CEX) forms and whether the training district or the year of training affected the nature of the feedback. Setting: Registrars' LPs from 2020 across five decentralised sites affiliated with the University of the Witwatersrand in South Africa were analysed. Methods: Two modified tools were used to evaluate the quantity of the written feedback in 38 learning plans and 57 mini-CEX forms. Descriptive statistics, Fisher's exact and Wilcoxon rank-sum tests were used for analysis. Content analysis was used to derive counts of areas of feedback. Results: Most learning plans (61.2%) did not refer to registrars' clinical knowledge or offer an improvement strategy (86.1%). The 'extent of supervisors' feedback' was rated as 'poor' (63.2%), with only 14.0% rated as 'good.' The 'some' and 'no' feedback categories in the mini-CEX competencies (p  0.001 to p = 0.014) and the 'extent of supervisors' feedback' (p  0.001) were significantly associated with training district. Feedback focused less on clinical reasoning and negotiation skills. Conclusion: Supervisors should provide specific and constructive narrative feedback and an action plan to improve registrars' future performance. Contribution: Supervisory feedback in postgraduate family medicine training needs overall improvement to develop skilled family physicians.